2022
DOI: 10.3390/pharmaceutics14102158
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Release Characteristics of Two Active Ingredients in Transdermal Patch Containing Lidocaine−Flurbiprofen Ionic Liquid

Abstract: Ionic liquids (ILs) have been proven to be an efficient technology for enhancing drug skin permeability. However, the question of whether the two components of ILs are released synchronously in transdermal preparations has remained unclear. Thus, this study aimed to investigate the release characteristics of two components of ILs and their underlying molecular mechanism. The ILs containing flurbiprofen (FLU) and lidocaine (LID) were synthesized and characterized. The four typical acrylates pressure sensitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…They found that release amounts of two drugs of API-ILs in four PSAs were all significantly different, proving that the two components were not released synchronously. This was because PSAs participated in inter-ionic interaction with the API-ILs and reduced the release of drugs [44] .…”
Section: Roles and Mechanismsmentioning
confidence: 99%
“…They found that release amounts of two drugs of API-ILs in four PSAs were all significantly different, proving that the two components were not released synchronously. This was because PSAs participated in inter-ionic interaction with the API-ILs and reduced the release of drugs [44] .…”
Section: Roles and Mechanismsmentioning
confidence: 99%
“…Furthermore, the adsorption of lidocaine onto cellulose is governed by Coulombic forces between the positively charged lidocaine molecules and the negatively charged cellulose surface. In aqueous environments, the ionized hydroxyl groups on cellulose create negatively charged sites, attracting the positively charged lidocaine molecules [85]. These electrostatic interactions, play a significant role in facilitating the adsorption of lidocaine onto BC, further enhancing its EE.…”
Section: Assessment Of Lidocaine Incorporation and Releasementioning
confidence: 99%
“…A study showed that ionic fluids are safe, contribute to the increase in skin permeability and are promising applications in the field of transdermal systems used in pain treatment [60].…”
Section: Transdermal System With Flurbiprofen and Lidocaine-ionic Liq...mentioning
confidence: 99%